Corneal Densitometry: Repeatability in Eyes With Keratoconus and Postcollagen Cross-Linking. Issue 6 (June 2016) - Pahuja, Natasha; Shetty, Rohit; Subbiah, Priya; Nagaraja, Harsha; Nuijts, Rudy M. M. A.; Jayadev, Chaitra
Abstract : Purpose: To assess the repeatability of densitometry, a measure of corneal haze, in the control (group I), keratoconic (group II), and postcollagen cross-linking (CXL, group III) eyes as measured on Scheimpflug imaging. Methods: Densitometry values for 160 eyes of 160 patients (50 eyes of 50 patients in group I, 50 eyes of 50 patients in group II, and 60 eyes of 60 patients in group III) were obtained for the 0- to 2-mm, 2- to 6-mm, and 6- to 10-mm zones of the anterior (up to 120 μm), posterior (posterior 60 μm), and central (between the anterior and posterior) cornea. The repeatability of these values was assessed by within-subject standard deviation, coefficient of repeatability, and coefficient of variation. Results: Range of within-subject standard deviation and coefficient of variation in the control group (0.2%–0.5% and 2%–4%, respectively) was significantly better (less variable) than those in the keratoconus group (0.4%–0.6% and 3%–5%). The same parameters in the post-CXL group (0.8%–3.8% and 7%–15%) were significantly worse (more variable) than that in the other 2 groups. The repeatability measures of densitometry were significantly worse in the central 0- to 2-mm zone compared with the other 2 zones and for the anterior region compared with the central and posterior regions of cornea in all the 3 groups. Conclusions: Consequent to the low repeatability in post-CXL eyes, densitometry should be used with caution to gauge response to treatment and visual outcomes in treated keratoconus eyes.